2018
DOI: 10.1080/02626667.2018.1557336
|View full text |Cite
|
Sign up to set email alerts
|

Empirical assessment of flood wave celerity–discharge relationships at local and reach scales

Abstract: An accurate comprehension of celerity (flood wave speed) dynamics is a key step for understanding flood wave propagation in rivers. We present the results of empirically estimated celerity values in 12 Brazilian rivers, and analyse the behaviour of celerity-discharge relationships (CxQ). Celerity was estimated with a reach-scale (RS) method, based on the peak travel time between stations; and with a local-scale (LS) method, based on the derivative of discharge-cross-section area relationships surveyed at gaugi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…been shown to improve celerity in hydrologic models, as flow exists the channel and generally encounters greater frictional resistance (Meyer et al, 2018).…”
Section: Channel Network and Nwm Routing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…been shown to improve celerity in hydrologic models, as flow exists the channel and generally encounters greater frictional resistance (Meyer et al, 2018).…”
Section: Channel Network and Nwm Routing Methodsmentioning
confidence: 99%
“…This compound channel was motivated by the limitation that channel flow cannot exit once it has entered the stream, leading to flashy behavior in areas that have natural attenuation in the floodplain and riparian zones. Adding in a floodplain has been shown to improve celerity in hydrologic models, as flow exists the channel and generally encounters greater frictional resistance (Meyer et al, 2018).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Flood wave celerity is a measure of flood wave speed (m s −1 ) (Meyer et al, 2018; Saleh et al, 2013). In this study, flood wave celerity is calculated using Equation by dividing the channel distance between two gauges on the same stream by the peak‐to‐peak travel time between these gauges (Fleischmann et al, 2016; Collischonn et al, 2017; Meyer et al, 2018).…”
Section: Regional Setting and Methodsmentioning
confidence: 99%
“…This was done to account for the expected hydrograph shape at different posi- For statistical analysis of upstream-to-downstream indicators, the data were cleaned to remove any spurious outliers. Flood wave celerity most commonly ranges between 0.25 and 10 m s À1 (Allen et al, 2018;Croke et al, 2014;Meyer et al, 2018;Turner-Gillespie et al, 2003). Sriwongsitanon et al (1998) showed that in-channel celerity of the Herbert River, Queensland, with a drainage area of 9400 km 2 reaches to around 10 m s À1 in a high flow.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…As its modest data requirements make it attractive for practical use, the Muskingum method is a popular alternative for routing flood waves through stream reaches. Therefore, various versions of the method, especially methods for estimating its parameters, are well established in the hydrological literature (e.g., McCarthy, 1938;Ponce and Yevjevich, 1978;Ponce and Theurer, 1982;Ponce and Chaganti, 1994;O'Donnell et al, 1998;Tang, et al, 1999;Birkhead and James, 2002;Al-Humoud and Esen, 2006;Perumal and Sahoo, 2008;Easa, 2013;Karahan et al, 2015;Niazkar et al, 2016;Afzali, 2016;Hamedi et al, 2016;Chulsang et al, 2017;Oliveira et al, n.d.;Asgari et al, 2018;Bai et al, 2018;Farzin et al, 2018;Kang and Zhou 2018;Meyer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%